2004
DOI: 10.1080/09718923.2004.11892427
|View full text |Cite
|
Sign up to set email alerts
|

Direct Foreign Investment and Firm-level Productivity in the Nigerian Agro/agro-allied Sector

Abstract: The acknowledged benefits of the DFI seems to be more than the demerits, and this seems to explain the current move of developing countries, seeking to attract private DFIs by removing the structural barriers and encouraging foreign investors. This study examines the impact of DFI on productivity at the firm-level in the agro/ agro-allied sector of the Nigerian economy as an example of developing countries. Data were obtained from agro/ agro-allied companies listed in the first tier market (comprising firms wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 8 publications
0
16
1
Order By: Relevance
“…FDI depicted positive relationship with financial market development while the real EXR depicts negative relationship with MKT. This was in contrast with earlier results (like Ayanwale and Bamire, 2001;Akinlo, 2004) which found a negative relationship between FDI and economic growth in Nigeria.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…FDI depicted positive relationship with financial market development while the real EXR depicts negative relationship with MKT. This was in contrast with earlier results (like Ayanwale and Bamire, 2001;Akinlo, 2004) which found a negative relationship between FDI and economic growth in Nigeria.…”
Section: Discussioncontrasting
confidence: 56%
“…Existing studies consider either the relationship between FDI and economic growth (Adelegan, 2000;Ayanwale and Bamire, 2001;Jerome and Ogunkola, 2004) or the relationship between financial market development and economic growth (Yartey, 2008;Yartey and Adjasi, 2007). Less attention has been paid to the possible causal nexus between FDI and stock market development in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that foreign private investment, domestic investment growth and net export growth positively influenced economic growth in Nigeria. Similarly, Ayanwale and Bamire (2004), and Ayashagba and Abachi (2002) found positive effect of FDI on economic growth for Nigeria.…”
Section: Some Empirical Evidencementioning
confidence: 92%
“…noted that export, labour, and human capital are positively related to economic growth in Nigeria. Ayanwale and Bamire (2001) assess the influence of FDI on firm level productivity in Nigeria and report a positive spillover of foreign firms on domestic firm's productivity. Oyinlola (1995) conceptualized foreign capital to include foreign loans, direct foreign investments and export earnings.…”
Section: Review Literaturesmentioning
confidence: 99%